Aumento do indicador global de eficiência por meio de melhoria no fluxo de materiais em uma linha de envase de produto alimentício - Malaquias, Amanda Radeck (2021)
In the current scenario, large companies are looking for ways to increase efficiency in their production processes to obtain greater profit margins, visibility on the national scene and greater commercial competitiveness. To assess progress in optimizing processes, the Global Equipment Efficiency (OEE) indicator can be used. To improve the OEE of a powdered food product filling line, in the case study of this concluding work, tools capable of reorganizing the production flow and eliminating losses in the movement of production inputs and people were applied. As a result, it was possible to increase the OEE of the filling line in question by up to 13%.